2019
DOI: 10.3390/ma12121912
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Pitting Corrosion of Al–Cu–Li Alloys Part III: Passivation Kinetics of AA2098–T851 Based on the Point Defect Model

Abstract: In this paper, the passivation kinetics of AA2098–T851 was investigated by a fundamental theoretical interpretation of experimental results based on the mixed potential model (MPM). The steady state passive layer formed on the AA2098–T851 in NaHCO3 solution in a CO2 atmosphere upon potentiostatic stepping in the anodic direction followed by stepping in the opposite direction was explored. Potentials were selected in a way that both anodic passive dissolution of the metal and hydrogen evolution reaction (HER) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…which is in accordance with our previous predictions [34,35]. The coefficient ∂L ss /∂V = 2.91 nm/V in Fig.…”
Section: Effect Of Applied Potential On the Passive Filmsupporting
confidence: 93%
See 2 more Smart Citations
“…which is in accordance with our previous predictions [34,35]. The coefficient ∂L ss /∂V = 2.91 nm/V in Fig.…”
Section: Effect Of Applied Potential On the Passive Filmsupporting
confidence: 93%
“…It is also found that, in all cases, k 2 is higher than k 3 , manifesting that the cation interstitial (Cr 3 + i ) rather than the oxygen vacancy (V ⋅⋅ o ) is the dominant point defect, and that the interstitial is responsible for the n-type semiconductor characteristic of the bl [24,26,56]. This is probably due to the larger radius of oxygen vacancy (V ⋅⋅ o ) as compared to Cr, Fe and Ni interstitial, which requires a higher vacancy formation energy [34]. The parameter k 1 controls the annihilation of the minority defect, the cation vacancy at m/bl interface (Fig.…”
Section: Effect Of Temperature On the Passive Filmmentioning
confidence: 96%
See 1 more Smart Citation
“…In the last years, many works were carried out in order to understand the corrosion mechanism and the corrosion resistance of the AA2024 alloy [18][19][20][21][22][23][24][25][26][27][28]12] and also of the Al-Cu-Li alloys [4,11,[29][30][31][32][33][34][35][36][37]. Recently, some researchers reported the effect of microstructure on the corrosion initiation in Al-Cu and Al-Cu-Li alloys [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. All these works demonstrated the higher susceptibility of these alloys to localised corrosion and the need for corrosion protection.…”
Section: Introductionmentioning
confidence: 99%
“…ese alloys displayed crystallographic corrosion morphology, selective attack of grain boundaries, and grain interiors [34,35]. Macdonald et al studied the pitting corrosion of 2098 Al-Li alloy, they thought the Al interstitial comprise the majority of the point defects in the barrier layer of this alloy, the formation of a passive layer had lower capacitance, which is associated with the point defect structure of the barrier layer [38]. Queiroz reported the EIS behavior of anodized and primer coated 2198 AL-Li alloy, they found the uncoated surface of this alloy showed higher pitting susceptibility, larger amounts of corrosion products formed on the anodized and primer coated surface of this alloy, and the diffusion was associated with large amounts of porous corrosion products on the exposed surface of this alloy to the corrosive environment [14].…”
Section: Introductionmentioning
confidence: 99%